Quality Measurement of Accurate-5 Accounting Software Using the Iso 9126 Model: Study on Accurate Workshop for D3 Computerized Accounting STMIK Mardira Students - Hasanah Tisna Amijaya; Ramlan Ramlan; Ganjar N Fajar (LPPM STMIK Mardira Indonesia, 2023)
This study aims to evaluate the degree of excellence of the Accurate-5 accounting software by employing the ISO-9126 model, which assesses six dimensions (primary characteristics) and associated attributes (secondary characteristics) of software quality. The researchers measured a sample of 41 participants who attended a workshop at STMIK Mardira Indonesia Bandung using the Accurate-5 software. The researchers gathered primary data using a questionnaire that utilized the Likert scale. The validity test results supported the validity of the items, as a value greater than 0.316 was found. The reliability test results demonstrated that all attributes have a high level of reliability, as each item had a Cronbach's alpha value greater than 0.7. The software quality evaluation findings utilizing the ISO 9126 standard indicate that all dimensions and attributes satisfy the